"Each race in its proper sphere": understanding Ottoman nation, race, and class in the travel narratives of Demetra Vaka Brown (1877–1946) and Leila Ahmed (1940–). Issue 1 (2nd January 2021) - Ahdifard, Unita
ABSTRACT: This article examines the lives and travel writings of two post-Ottoman women writers, Demetra Vaka Brown (1877–1946), a former Ottoman Greek who immigrated to the United States in the late nineteenth century, and Leila Ahmed (1940–), an Egyptian-American scholar whose family was of Turko-Circassian origins. While Vaka Brown's The Unveiled Ladies of Stamboul (1923) is a post-World War I memoir that nostalgically reminisces on the Ottoman era, Ahmed's A Border Passage (1999) examines the political twists and turns in twentieth-century Egypt, and their implications for Ahmed's family. Both women grapple with their Ottoman heritage, exploring constructions of gender as they intersect with Ottoman religious beliefs, class strata, and post-Ottoman nationalisms.